Fast Peel‐Off Ultrathin, Transparent, and Free‐Standing Films Assembled from Low‐Dimensional Materials Using MXene Sacrificial Layers and Produced Bubbles (Small Methods 3/2022). Issue 3 (21st March 2022) - Ling, Zheng; Wang, Fuqiang; Shi, Changrui; Wang, Zhiyu; Fan, Xuanhui; Wang, Lu; Zhao, Jiafei; Jiang, Lanlan; Li, Yanghui; Chen, Cong; Tang, Dawei; Song, Yongchen
Abstract : Front Cover In article number 2101388, Ling, Song, and coworkers developed a novel and scalable method that enables one to rapidly and intactly detach ultrathin and transparent films assembled from various low‐dimensional materials. By adopting a layer of MXenes as the interlayer and foaming agent, ultrathin films can be peeled off in tens of seconds. The demonstrated method allows for making multifunctional films with ultrathin, transparent, and flexible features.